Dietary replacement of soybean meal with black soldier fly larvae meal in juvenile Labeo rohita and Catla catla: Effects on growth, nutritional quality, oxidative stress biomarkers and disease resistance. - Shafaq Fatima; Ayesha Afzal; Hamna Rashid; Saba Iqbal; Rosheen Zafar; Komal Khalid; Ayman Rauf; Maryam Majeed; Aqsa Malik; Chris G Carter (PLoS ONE, 2023)
This experiment aimed to investigate the effects of partial substitution of crude protein from soybean meal (SBM) with black soldier fly (Hermetia illucens) larvae meal (BSFLM) in juvenile rohu (Labeo rohita) and catla (Catla catla). Four isonitrogenous diets (23% crude protein) were formulated to replace 0% (T0), 40% (T40), 80% (T80) and 100% (T100) crude protein from SBM with BSFLM. Triplicate groups of each species (10 fish per replicate) were fed in an eight week growth experiment. After final sampling (n = 20 fish per dietary group), the remaining fish were exposed to bacterial (Staphylococcus aureus) challenge (0.80 CFU/ml) for 15 days. Rohu fed with BSFLM substituted diets showed significantly higher growth and feed conversion ratio as compared to those in T0. Catla fed with BSFLM substituted diets showed slightly higher growth indices. The growth response of rohu to BSFLM substitution was better than that noted in catla in all groups. The chemical composition, amino acids and fatty acids profile, haematological and biochemical parameters, levels of liver function enzymes measured in T0, T40, T80 and T100 were similar between four dietary groups in both species. However, the maximum value of cholesterol and triglycerides were noted in T100 both in catla and rohu. The values of lauric acid, α-linolenic acid, decosahexanoic acid, n3:n6 fatty acids ratio progressively increased with dietary increase of BSFLM in both species. At end of the growth experiment, the levels of catalase, superoxide dismutase and lysozyme increased linearly with the inclusion of BSFLM in both species while malondialdehyde showed similar values between different groups. However, catalase, and superoxide dismutase increased (T0<T40<T80<T100) in both rohu and catla after exposure to bacterial challenge while malondialdehyde remained almost the same. These biomarkers indicate that substitution of SBM with BSFLM up to 100% improved disease resistance in both species against gram-positive bacteria.